Risk factors for the progression of trachomatous scarring in a cohort of women in a trachoma low endemic district in Tanzania - Meraf A. Wolle (Public Library of Science (PLoS), 2021)
Background Trachoma, a chronic conjunctivitis caused by Chlamydia trachomatis, is the leading infectious cause of blindness worldwide. Trachoma has been targeted for elimination as a public health problem which includes reducing trachomatous inflammation—follicular prevalence in children and reducing trachomatous trichiasis prevalence in adults. The rate of development of trachomatous trichiasis, the potentially blinding late-stage trachoma sequelae, depends on the rate of trachomatous scarring development and progression. Few studies to date have evaluated the progression of trachomatous scarring in communities that have recently transitioned to a low trachomatous inflammation—follicular prevalence. Methodology/Principal findings Women aged 15 and older were randomly selected from households in 48 communities within Kongwa district, Tanzania and followed over 3.5 years for this longitudinal study. Trachomatous inflammation—follicular prevalence was 5% at baseline and at follow-up in children aged 1–9 in Kongwa, Tanzania. 1018 women aged 15 and older had trachomatous scarring at baseline and were at risk for trachomatous scarring progression; 691 (68%) completed follow-up assessments. Photographs of the upper tarsal conjunctiva were obtained at baseline and follow-up and graded for trachomatous scarring using a previously published four-step severity scale. The overall cumulative 3.5-year progression rate of scarring was 35.3% (95% CI 31.6–39.1). The odds of TS progression increased with an increase in age in women younger than 50, (OR 1.03, 95% CI 1.01–1.05, p = 0.005) as well as an increase in the household poverty index (OR 1.29, 95% CI 1.13–1.48, p = 0.0002). Conclusions/Significance The 3.5-year progression of scarring among women in Kongwa, a formerly hyperendemic now turned hypoendemic district in central Tanzania, was high despite a low active trachoma prevalence. This suggests that the drivers of scarring progression are likely not related to on-going trachoma transmission in this district. Author summary Trachoma, a chronic conjunctivitis caused by Chlamydia trachomatis, presents with follicles (trachomatous inflammation—follicular, TF) in children which leads to trachomatous conjunctival scarring (TS) in young adults. TS can progress to the in-turning of eyelashes, trachomatous trichiasis (TT) which places individuals at high risk of irreversible vision loss. Few studies to date have evaluated the progression of TS in communities that have recently transitioned to a low trachoma prevalence. We studied the progression of TS in women in Kongwa, Tanzania a district that recently transitioned to a low prevalence of trachoma. We found that the overall cumulative progression of scarring was 35.3% over 3.5 years. The scarring progression rate observed is very similar to what we observed a decade prior in Kongwa when the trachoma prevalence was very high. Our findings suggest that once scarring has developed it continues to progress irrespective of the current trachoma environment. This has potential ramifications for trachoma elimination efforts. An area could achieve the elimination of TF and still have to deal with scarring progression, which may lead to the development of TT. If this occurs: 1) elimination of TT will be delayed which will delay the overall elimination of trachoma as a public health problem, and 2) the limited resources available to elimination programs may need to be re-allocated.